2022
DOI: 10.3390/jof8060550
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Plasma Membrane H+-ATPases of Ustilago maydis

Abstract: Plasma membrane H+-ATPases of fungi, yeasts, and plants act as proton pumps to generate an electrochemical gradient, which is essential for secondary transport and intracellular pH maintenance. Saccharomyces cerevisiae has two genes (PMA1 and PMA2) encoding H+-ATPases. In contrast, plants have a larger number of genes for H+-ATPases. In Ustilago maydis, a biotrophic basidiomycete that infects corn and teosinte, the presence of two H+-ATPase-encoding genes has been described, one with high identity to the funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These results suggest that the accumulation of melanin did not affect the cell division processes and vegetative growth. Furthermore, deletion of the pma1 gene did not affect the glucose or oxygen consumption [31]. On the other hand, we noticed that the ∆PMA1 mutant was stable after long periods of storage at −80 • C.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These results suggest that the accumulation of melanin did not affect the cell division processes and vegetative growth. Furthermore, deletion of the pma1 gene did not affect the glucose or oxygen consumption [31]. On the other hand, we noticed that the ∆PMA1 mutant was stable after long periods of storage at −80 • C.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast, in the yeast Saccharomyces cerevisiae, only one gene (PMA1) is expressed [45]. In a recent publication about the U. maydis H+ ATPase, mutation of any of these genes did not affect the proton pumping or internal pH changes [31].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are two plasma membrane H + -ATPases, PMA1 and PMA2, in fungi [10][11][12]. Many studies have shown that PMA1 is localized in lipid microdomains of the plasma membrane and plays an important role in cell growth and virulence in pathogenic fungi [16,17]. However, PMA2 is generally believed to have little effect on the growth and pathogenicity of fungi due to its extremely low expression in cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…The structure and function of plasma membrane H + -ATPases, especially PMA1, have been extensively studied in some fungi, such as Fusarium graminearum, Valsa mali, and Ustilago maydis [14,15]. Most studies have shown that PMA1 is localized to lipid microdomains of the plasma membrane and plays a central role in the regulation of the pH homeostasis system, and it is responsible for cell growth and virulence in pathogenic fungi [16,17], such as PMA1 in Neurospora crassa [18], PMA1 in F. graminearum [19], PMA2 in Magnaporthe grisea [20], PMA1 in Leptosphaeria maculans [21], and PMA1 in U. maydis [17]. Unlike PMA1, it is generally believed that PMA2 has little effect on the growth and pathogenicity of fungi due to its extremely low expression in cells [22].…”
Section: Introductionmentioning
confidence: 99%